Acceptor‐Substituted S, N‐Heteropentacenes of Different Conjugation Length: Structure–Property Relationships and Solar Cell Performance. (30th April 2015) - Kast, Hannelore; Mishra, Amaresh; Schulz, Gisela L.; Urdanpilleta, Marta; Mena‐Osteritz, Elena; Bäuerle, Peter
Abstract : The synthesis, optoelectronic, and photovoltaic properties of novel acceptor–donor–acceptor (A–D–A) based π‐conjugated functional molecules1 –3, comprising a planar S, N ‐heteropentacene as central donor substituted with various terminal acceptor units, such as 1, 1‐dicyanovinylene (DCV) and 1‐(1, 1‐dicyanomethylene)‐cyclohex‐2‐ene (DCC), are reported. The structural variation of the end groups provides molecules1 –3 with gradually increased π‐conjugation due to a rising number of double bonds, which comes from the DCC unit(s). From optoelectronic investigation, structure–property relationships are deduced and the novel A–D–A heteropentacenes1 –3 are implemented as photoactive donor component in solution‐processed bulk heterojunction solar cells together with [6, 6]‐phenyl‐C61 ‐butyric acid methyl ester as acceptor. The structural variation in the S, N ‐heteropentacenes leads to clear trends in the photovoltaic performance and power conversion efficiencies of up to 4.9% are achieved. Furthermore, due to extension of the double bonds a clear trade‐off between the open circuit voltage ( V OC ) and the short circuit current density ( J SC ) values is observed. The role of additives on the optimization of the nanoscale morphology and device performance is investigated. The findings presented herein demonstrate that depending on the types of materials the additive may have significantly different effects on the active layer morphology and the device performance. Abstract : A new class of A–D–A‐type molecular donor materials based on S, N ‐heteropentacene is developed for incorporation into solution‐processed bulk heterojunction solar cells providing promising power conversion efficiencies of 3.1–4.9%. The extension of the π‐system and increase in the highest occupied molecular orbital energy level provide direct correlation for the improved short circuit current ( J SC ) and decreased open circuit voltage ( V OC ) values.